2013
DOI: 10.1021/jp402008w
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Single- and Bilayer ZnO on Au(111) and Interaction with Copper

Abstract: The stoichiometric single-and bilayer ZnO(0001) have been prepared by reactive deposition of Zn on Au(111) and studied in detail with X-ray photoelectron spectroscopy, scanning tunneling microscopy, and density functional theory calculations. Both single-and bilayer ZnO(0001) adopt a planar, graphite-like structure similar to freestanding ZnO(0001) due to the weak van der Waals interactions dominating their adhesion with the Au(111) substrate. At higher temperature, the single-layer ZnO(0001) converts graduall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
117
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(131 citation statements)
references
References 47 publications
12
117
2
Order By: Relevance
“…Table I. The agreement with experimental values for sub-monolayer ZnO islands is good (Ag, 35,36 Pd, 37 Pt, 38 Au, 39 Cu (brass), 40 and Ru (0001) 41 ). The coincidence structures for which the ZnO in-plane lattice parameter is closest to that of the free-standing structure gives the lowest formation energy.…”
supporting
confidence: 67%
“…Table I. The agreement with experimental values for sub-monolayer ZnO islands is good (Ag, 35,36 Pd, 37 Pt, 38 Au, 39 Cu (brass), 40 and Ru (0001) 41 ). The coincidence structures for which the ZnO in-plane lattice parameter is closest to that of the free-standing structure gives the lowest formation energy.…”
supporting
confidence: 67%
“…Examples include Pd(111) [17], Pt(111) [18,19], Au(111) [20], Ag(111) [4,21,22], Cu(111) [22] and Brass(111) [23]. Prior to deposition, the surfaces of the metal substrates were cleaned by mechanical polishing [4] and by cycles of Ar + ion sputtering followed by annealing in UHV, at 1000 K for Pd [17], 750 K for Ag [4], 670 K [21] or 700 K for Au [20], and 1200 K for Pt [19]. In some cases [17][18][19]22], an annealing step was carried out in the presence of O 2 at high temperature (700-800 K) to remove residual carbon.…”
Section: G-zno Growth Over a Metal Substratementioning
confidence: 99%
“…g-ZnO layers can be obtained by first depositing pure Zn at room temperature on to a clean metal substrate by heating a Zn rod using a Knudsen cell [17,21]; in other cases, pulsed laser deposition [4], an electron beam-assisted evaporator [20] or applied current through a thoriated tungsten wire wrapped around the Zn rod can be used [18,19,22]. When oxygen is injected, it is done so at relatively high pressures ranging from~10 −8 and~10 −5 mbar either during or after Zn deposition at room temperature, followed by an annealing step in UHV (the annealing temperature depends on the metal substrate and typically varies between 550 K and 680 K).…”
Section: G-zno Growth Over a Metal Substratementioning
confidence: 99%
See 1 more Smart Citation
“…However, our studies of FeO(111) [10] and ZnO(0001) [13] films on Pt(111) showed that such a monolayer structure is unstable under realistic pressure conditions. Moreover, other DFT studies of ZnO(0001) films on noble metals (Pd(111) [35], Cu(111) [36], and Au(111) [37]) and experimental data available for ZnO/Ag(111) [21] revealed substantial interlayer relaxations such that ultrathin ZnO films resemble the co-planar sheets in the boron nitride (or graphite) structure, and they are only weakly bound to a metal support, in contrast to the models used by Sun et al [34].…”
Section: Reactivity Of Metal-supported Zno(0001) Films: Comparisonmentioning
confidence: 99%